2015
DOI: 10.3389/fmicb.2015.00582
|View full text |Cite
|
Sign up to set email alerts
|

Distinct soil bacterial communities along a small-scale elevational gradient in alpine tundra

Abstract: The elevational diversity pattern for microorganisms has received great attention recently but is still understudied, and phylogenetic relatedness is rarely studied for microbial elevational distributions. Using a bar-coded pyrosequencing technique, we examined the biodiversity patterns for soil bacterial communities of tundra ecosystem along 2000–2500 m elevations on Changbai Mountain in China. Bacterial taxonomic richness displayed a linear decreasing trend with increasing elevation. Phylogenetic diversity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
78
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 74 publications
17
78
4
Order By: Relevance
“…Similarly, Wang et al revealed a hollow elevational diversity pattern of fungi in Tibet related to soil pH (Wang et al, 2015b). The monotonically decreasing diversity pattern in the grassland was consistent with a recent study in tundra where soil carbon and nitrogen were considered as the limiting factors (Shen et al, 2015).…”
Section: Different Elevational Patterns Of Bacterial Diversity Above supporting
confidence: 81%
See 1 more Smart Citation
“…Similarly, Wang et al revealed a hollow elevational diversity pattern of fungi in Tibet related to soil pH (Wang et al, 2015b). The monotonically decreasing diversity pattern in the grassland was consistent with a recent study in tundra where soil carbon and nitrogen were considered as the limiting factors (Shen et al, 2015).…”
Section: Different Elevational Patterns Of Bacterial Diversity Above supporting
confidence: 81%
“…Ding et al also demonstrated soil temperature as the main factor influencing microbial composition around the timberline (Ding et al, 2015). Total variation explained by soil temperature combined with available phosphorus, pH, and clay content reached 67% in the meadow, implying niche-based environmental filtering processes strongly structuring bacterial communities along the elevational gradient (Shen et al, 2015). However, the explanatory power of bacterial diversity in the forest is much lower than that in the meadow.…”
Section: )mentioning
confidence: 99%
“…5). The mean DOC (from 238 to 474 mg kg -1 ) recorded in our research site was comparable to that reported by Shen et al (2015) (~400 mg kg -1 ) in the Qinghai-Tibetan Plateau. The mean DON (from 11.7 to 24.6 mg kg -1 ) was on the same order of magnitude as that observed by Gao et al (2015) (13.9 mg kg -1 ) (Fig.…”
Section: Soil N and C Forms In Relation To The Pedoclimatic Conditionsupporting
confidence: 72%
“…The mean N micr (from 52.5 to 160 mg kg -1 ) was comparable to that observed by Williams et al (2007), but higher than that reported by Hood et al (2003) (from ~9 to 27 mg kg -1 ) for the Colorado Rockies, and the C micr had values comparable or higher than other alpine and arctic areas (Fig. 7) (e.g., Edwards and Jefferies, 2013;Shen et al, 2015). To date, according to our knowledge, with the exception of works about the interannual changes in CO 2 fluxes in both alpine (e.g., Saleska et al, 1999;Kato et al, 2006) and arctic tundra (e.g., Harazono et al, 2003), very little is known about the interannual variability of soil N and C forms in alpine tundra soils.…”
Section: Soil N and C Forms In Relation To The Pedoclimatic Conditionsupporting
confidence: 66%
“…Furthermore, the soil composition can change over an elevation gradient due to the geological and/or land use history of mountain areas, giving each mountain ecosystem a unique geochemical profile that shapes the local endemic bacterial communities. For instance, the soil bacterial communities along the Changbai Mountain in China were driven by the soil total carbon and nitrogen, the C:N ratio, and dissolved organic carbon, which changed across the elevation strata (19), whereas in the Colorado Rockies, soil pH and elevation were strongly negatively correlated with each other (3). Elevational differences may also relate to human impact, as was shown in a study by Marini and coworkers (20) on the effect of farm size in the Italian Alps.…”
mentioning
confidence: 99%